2022
DOI: 10.3390/app12073589
|View full text |Cite
|
Sign up to set email alerts
|

Computational Characterization of Turbulent Flow in a Microfluidic Actuator

Abstract: In this contribution, an unsteady numerical simulation of the flow in a microfluidic oscillator has been performed. The transient turbulent flow inside the device is described by the Unsteady Reynolds Averaged Navier–Stokes equations (URANS) coupled with proper turbulence models. The main characteristics of the complex fluid flow inside the device along one oscillation cycle was analyzed in detail, including not only velocity contours but also the pressure and turbulent kinetic energy fields. As a result, two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In our previous work, we used the SST k –ω model and found that the model under-predicted the jet oscillation frequency by almost 10%. Similar underprediction was reported by Bobusch et al and Hossain et al However, overprediction of jet oscillation frequency is also reported in the literature. ,, Laín et al used the SST k –ω model for the 2D case and found that their predicted oscillation frequencies obtained were within the experimental error bars reported by Bobusch et al and 3D hybrid DES simulation by Baghaei et al Overprediction of the jet oscillation frequency was also reported with the use of k –ε, RNG, k –ε, and k –ω compared to SST k –ω.…”
Section: Computational Modelingsupporting
confidence: 78%
“…In our previous work, we used the SST k –ω model and found that the model under-predicted the jet oscillation frequency by almost 10%. Similar underprediction was reported by Bobusch et al and Hossain et al However, overprediction of jet oscillation frequency is also reported in the literature. ,, Laín et al used the SST k –ω model for the 2D case and found that their predicted oscillation frequencies obtained were within the experimental error bars reported by Bobusch et al and 3D hybrid DES simulation by Baghaei et al Overprediction of the jet oscillation frequency was also reported with the use of k –ε, RNG, k –ε, and k –ω compared to SST k –ω.…”
Section: Computational Modelingsupporting
confidence: 78%
“…Thus, the hydraulic characteristics of curved flow have been an important subject in river dynamics. Research on open channel bends mainly focuses on water surface line, three-dimensional velocity, pressure distribution, turbulent kinetic energy, and shear stress [1][2][3][4][5].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Their results indicated that a harmonically oscillating primary flow was generated, increasing the mixing entrainment and momentum transfer while reducing the pressure in the suction and mixing chambers. A microfluidic actuator was studied at high Reynolds numbers in [31], where 2D-URANS simulations along with experimental results and a final 3D CFD simulation was performed. Coherent structures as well as turbulent kinetic energy fields and velocity contours were used to unveil the associated complex fluid dynamics.…”
Section: Introductionmentioning
confidence: 99%